Surface peptide functionalization of zeolitic imidazolate framework-8 for autonomous homing and enhanced delivery of chemotherapeutic agent to lung tumor cells - Nurul Akmarina, Mohd Abdul Kamal; Emilia, Abdulmalek; Sharida, Fakurazi; Cordova, Kyle E.; Mohd Basyaruddin, Abdul Rahman (Royal Society of Chemistry, 2021)
Chemotherapeutic agents used in treating certain cancer types operate in a non-selective manner tending to accumulate in normal, healthy tissue when high doses are used. To mitigate the toxicity effect resulting from this, there is an urgent need to develop active nano delivery systems capable of regulating optimal doses specifically to cancer cells without harming adjacent normal cells. Herein, we report a versatile nanoparticle – zeolitic imidazolate framework-8 (nZIF-8) – that is loaded with a chemotherapeutic agent (gemcitabine; GEM) and surface-functionalized with an autonomous homing system (Arg-Gly-Asp peptide ligand; RGD) via a straightforward, one-pot solvothermal reaction. Successful functionalization of the surface of nZIF-8 loaded GEM (GEM⊂nZIF-8) with RGD was proven by spectroscopic and electron microscopy techniques. This surface-functionalized nanoparticle (GEM⊂RGD@nZIF-8) exhibited enhanced uptake in human lung cancer cells (A549), compared with non-functionalized GEM⊂nZIF-8. The GEM⊂RGD@nZIF-8, experienced not only efficient uptake within A549, but also induced obvious cytotoxicity (75% at a concentration of 10 μg mL−1) and apoptosis (62%) after 48 h treatment when compared to the nanoparticle absent of the RGD homing system (GEM⊂nZIF-8). Most importantly, this surface-functionalized nanoparticle was more selective towards lung cancer cells (A549) than normal human lung fibroblast cells (MRC-5) with a selectivity index (SI) of 3.98. This work demonstrates a new one-pot strategy for realizing a surface-functionalized zeolitic imidazolate framework that actively targets cancer cells via an autonomous homing peptide system to deliver a chemotherapeutic payload effectively.